Modus Operandi of “Rarest of the Rare Case” For Capital Sentence: A Critical Testing of the Prudence of the Judicial Doctrine - Sudarshan Verma,; Gargi Whorra, (AG Volumes, 2026)
Death Penalty is the most severe form of punishment under penal scheme in India. Death penalty is a judicially mandated form of killing wherein the punishment is taking of the life of the convict. The moralist advocate for death penalty as a necessary deterrent for the most heinous crimes inflicted upon society, whereas the progressive humanists claim capital punishment to be merely a court mandated murder. The Hon’ble Supreme Court of India has evolved a formula to inflict capital punishment limited to the “rarest of rare cases”. In fact, the doctrine of rarest of rare case appears superfluous, vague and even incomplete on first blush. The judicial approach in inflicting the sentence has become subjective particularly in death penalties. A vast discretion is used by the judiciary thereby resulting in uncertainty of judgments. This chapter is an attempt to test the application of this judicial doctrine in similar cases differently. For this testing some relevant case laws are also discussed and analysed. The chapter is divided in five parts that aims to introduce the topic, overview of the punishment of death penalty in India, judicial creativity pertaining to death penalty in India, fallacies in death penalty jurisprudence in India, conclusion and relevant suggestions.